Ultra-Performance Liquid Chromatography-Mass Spectrometry-Based Untargeted Metabolomics Reveals the Key Potential Biomarkers for Castor Meal-Induced Enteritis in Juvenile Hybrid Grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Amoah, Kwaku; Dong, Xiao-hui; Tan, Bei-ping; Zhang, Shuang; Chi, Shu-yan; Yang, Qi-hui; Liu, Hong-yu; Yan, Xiao-bo; Yang, Yuan-zhi; Zhang, Haitao (Frontiers in Nutrition, 2022)
The intensification of aquaculture to help curb global food security issues has led to the quest for more economical new protein-rich ingredients for the feed based aquaculture since fishmeal (FM, the ingredient with the finest protein and lipid profile) is losing its acceptability due to high cost and demand. Although very high in protein, castor-meal (CM), a by-product after oil-extraction, is disposed-off due to high presence of toxins. Concurrently, the agro-industrial wastes’ consistent production and disposal are of utmost concern; however, having better nutritional profiles of these wastes can lead to their adoption. This study was conducted to identify potential biomarkers of CM-induced enteritis in juvenile hybrid-grouper (Epinephelus fuscoguttatus♀×Epinephelus lanceolatus♂) using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) alongside their growth and distal intestinal (DI) health evaluation. Three-hundred and sixty (360) fish (initial weight=9.13±0.01g) were randomly assigned into three groups, namely, fish-meal (FM) (control), 4% CM (CM4), and 20% CM (CM20). After the 56-days feeding-trial, the DI tissues of FM, CM4, and CM20 groups were collected for metabonomics analysis. Principal components analysis and partial least-squares discriminant-analysis (PLS-DA, used to differentiate the CM20, and CM4, from the FM group with satisfactory explanation and predictive ability) were used to analyse the UPLC-MS data. The results revealed a significant improvement in the growth, DI immune responses and digestive enzyme activities, and DI histological examinations in the CM4 group than the others. Nonetheless, CM20 replacement caused DI physiological damage and enteritis in grouper as shown by AB-PAS staining and scanning electron microscopy examinations, respectively. The most influential metabolites in DI contents identified as the potential biomarkers in positive and negative modes using the metabonomics UPLC-MS profiles were 28 which included 5 organoheterocyclic compounds, 7 lipids and lipid-like molecules, 7 organic oxygen compounds, 2 benzenoids, 5 organic acids and derivatives, 1 phenylpropanoids and polyketides, and 1 from nucleosides, nucleotides, and analogues superclass. The present study identified a broad array of DI tissue metabolites that differed between FM and CM diet, which provides a valuable reference for further managing fish intestinal health issues. A replacement level of 4% is recommended based on the growth and immunity of fish.